Hypertonic saline in people with cystic fibrosis: review of comparative studies and clinical practice - Vito Terlizzi; Eleonora Masi; Michela Francalanci; Giovanni Taccetti; Diletta Innocenti (BMC, 2021)
Abstract Cystic fibrosis (CF) is a multisystem disorder, caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. These cause a reduced secretion of chloride, a marked absorption of sodium and, therefore, of water, through the epithelium, resulting in the formation of thickened secretions in organs such as lung or pancreas. These viscous secretions lead to airway obstruction, chronic infection and inflammation resulting in progressive lung damage, bronchiectasis and eventual respiratory failure. Although the average life expectancy has increased over the last 30 years, lung disease is the most common cause of death in people with CF. For these reasons, the improvement of sputum clearance is a major therapeutic aim in CF and early initiation of airway clearance is widely recommended and implemented. Symptomatic mucolytic therapy today is mainly based on inhalation of DNase, hypertonic saline or mannitol, in combination with physiotherapy. Mucolytic agents break down the gel structure of mucus and therefore decrease its elasticity and viscosity, reducing the pulmonary exacerbation frequency and to improve and stabilize lung function. Nevertheless, high quality studies comparing these mucolytic drugs are still few, and the individual experiences of patients and caregivers explain the high variability of their use globally. This review will summarize the current knowledge on hypertonic saline in the treatment of CF lung disease. Furthermore, we report the real-world prescription of inhaled mucolytic agents in CF.